An experimental study to evaluate the Fluobeam 800 imaging system for fluorescence-guided lymphatic Imaging and sentinel node biopsy - Hirche, Christoph; Engel, Holger; Harhaus-Wähner, Leila; Cognie, Juliette; Hünerbein, Michael; Lehnhardt, Marcus; Kremer, Thomas (Surgical innovation, 2013)
Background. Visualization of the lymphatic system is challenging. Lymphatic imaging is a crucial diagnostic tool for benign and malignant lymphatic pathologies. Fluorescence-guided imaging allows selective lymphatic mapping and sentinel lymph node (SLN) identification. There are a few fluorescence systems, but some drawbacks remain due to technical and ergonomic aspects. The aim of this study was to evaluate the feasibility of the new Fluobeam 800 imaging system. Methods. After approval by the ethics committee, the system was evaluated for lymphography and SLN biopsy in an animal model. Five pigs each with 4 lymph node (LN) stations (n = 20 LN stations) were subjected to lymphatic imaging using indocyanine green (ICG). Additionally, the use of ICG was compared with ICG adsorbed to human serum albumin (ICG-HSA). Lymphatic vessels and SLN identification rates were measured. Results. After injection, a clear fluorescence signal of the lymphatic vessels was visualized leading to the LN station. Overall, ICG fluorescence imaging identified a mean of 2.0 lymphatic vessels and 1.1 (range = 1-2) SLN in 20 of 20 LN stations. Reverse lymphography was feasible. A clinical difference in resolution was not detected between use of ICG-HSA and ICG. Conclusion. This is the first study analyzing the feasibility of the Fluobeam 800 imaging system allowing transcutaneous real-time imaging. It enables detection of the SLN by fluorescence retention with increased detection depth and resolution. After fixation to the ceiling, the ergonomics advanced for simultaneous field navigation and dissection. The new system can be applied for lymphatic imaging for lympatico-reconstructive surgery and SLN biopsy.
Gesehen am 31.05.2021
First Published December 27, 2012